Glycine-Histidine-Lysine (GHK) Alleviates Neuronal Apoptosis Due to Intracerebral Hemorrhage via the miR-339-5p/VEGFA Pathway - Zhang, Heyu; Wang, Yanzhe; He, Zhiyi (Frontiers in Neuroscience, 2018)
GHK is a human tripeptide that has been shown to enhance wound healing, exert neuroprotective effects against neurodegenerative disease, and improve tissue regeneration. We aimed to examine whether GHK can alleviate injury due intracerebral hemorrhage (ICH). Water content, neuronal apoptosis, and neurological deficit scores were examined in a rat model of ICH following intraperitoneal injection of GHK. Apoptosis was evaluated via caspase-3 immunohistochemistry and Nissl staining. We also examined the effect of GHK on the expression of related proteins in SH-SY5Y cells via Western blotting. The expression of miR-339-5p was examined via real-time polymerase chain reaction (RT-PCR) analyses. GHK improved neurological deficits in ICH rats. GHK treatment also reduced water content in the brain and inhibited neuronal apoptosis both in vivo and in vitro. Furthermore, the effects of GHK were associated with the downregulation of miR-339-5p, which partially reversed the neuroprotective effects of GHK treatment. Our findings suggested that the p38 MAPK pathway is involved in the GHK-induced regulation of mir-339-5p, and that the miR-339-5p/VEGFA axis plays a role in neuronal apoptosis following ICH injury. These findings indicate that GHK may represent a novel therapeutic strategy for ICH.